Effective esl vocabulary teaching techniques - Sharapova, Gulshan (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article analyses the importance and advantages of vocabulary methods in teaching English as a one of the essential feature in EFL classes and its importance on learner’s acquiring language. In this article,several different vocabulary methods for teaching ESL classes are outlined